Evaluation of Effectiveness and Multi-Scenario Analysis of Land Use Development Strategies and Ecological Protection Redlines on Carbon Storage in the Great Bay Area of China Using the PLUS-InVEST-PSM Model - Yuhao Jin; Yan Li; Han Zhang; Xiaojuan Liu; Hong Shi (Land)
Land use change is a key factor affecting the carbon storage of terrestrial ecosystems. Most studies focus on formulating different land development strategies to mitigate the adverse impacts of land development, while fewer discuss the effectiveness of these strategies. In the context of varying socio-economic development and limited budgets for ecological conservation, evaluating effectiveness is essential for selecting the most suitable land development strategy. This research proposed a Patch-Generating Land Use Simulation-Integrated Valuation of Ecosystem Services and Tradeoffs–Propensity Score Matching (PLUS-InVEST-PSM) model to evaluate the effectiveness of different land use development strategies in the Greater Bay Area of China as a case study. Specifically, this study analyzed the historical land use changes from 2000 to 2020 and mapped the multi-scenario patterns of land use and carbon storage with the PLUS and the InVEST models from 2030 to 2050. Then, this study employed the PSM model, along with a series of criteria (i.e., similar ecological backgrounds and parallel historical trends), to evaluate the effectiveness of the ecological development strategy and ecological protection redlines on carbon storage compared with the natural development strategy. The results indicate that the ecological development strategy and the ecological protection redline can prevent the decline in carbon storage. However, in the ecological development strategy, implementing the ecological redline policy may hinder the growth of carbon storage within the ecological redline area. Compared with the PLUS-InVEST-PSM model, the comparison between the subregions could underestimate the efficiencies of evaluation, partly due to underestimating the negative impact of urban development on carbon storage. These findings will help governments develop comprehensive and systematic land use policies to achieve carbon peaking and carbon neutrality goals. Also, the approach would help to further explore the broader impacts of land use development strategies on the overall regional ecological environment, such as biodiversity and ecosystem services.